2011
DOI: 10.1074/jbc.m111.271726
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Mint3/Apba3 Gene in Mice Abrogates Macrophage Functions and Increases Resistance to Lipopolysaccharide-induced Septic Shock

Abstract: Two major metabolic systems are usually used to generate ATP: oxidative phosphorylation (OXPHOS) in the mitochondria and glycolysis. Most types of cells employ OXPHOS for ATP production during normoxia but then shift energy production from OXPHOS to glycolysis when exposed to hypoxia. Hypoxia-inducible factor-1 (HIF-1) is the master transcription factor regulating this metabolic shift. On the other hand, macrophages are unique in making use of glycolysis for ATP generation constitutively even during normoxia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…Previously, we had reported that Apba3 −/− BM-derived macrophages are defective in chemotaxis due to reduced glycolytic production of ATP that is caused by low HIF activity (20). We found that the glycolysis inhibitor 2-deoxyglucose (2-DG) abolished in vivo chemotaxis of IMs toward CCL2 (Fig.…”
Section: Apba3 Supports Metastasis Formation Via Induction Of E-selectinmentioning
confidence: 61%
See 4 more Smart Citations
“…Previously, we had reported that Apba3 −/− BM-derived macrophages are defective in chemotaxis due to reduced glycolytic production of ATP that is caused by low HIF activity (20). We found that the glycolysis inhibitor 2-deoxyglucose (2-DG) abolished in vivo chemotaxis of IMs toward CCL2 (Fig.…”
Section: Apba3 Supports Metastasis Formation Via Induction Of E-selectinmentioning
confidence: 61%
“…CCL2 recruits both metastasis-promoting IMs and -suppressive NEs (4,14), although only recruitment of IMs was affected in tumor-inoculated Apba3 −/− mice (Fig. 5C), perhaps because glycolytic regulation by APBA3 is specific for macrophages but not for NEs (20). Thus, APBA3 is a possible target for metastasis suppression by targeting monocyte/macrophage-specific machineries.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations